From Economic Competition to Military Combat: Export Similarity and International Conflict. (August 2017) - Chatagnier, J. Tyson; Kavaklı, Kerim Can
The vast majority of the extant literature on trade and conflict focuses on bilateral trade to determine whether commerce has a pacifying effect upon pairs of states. We argue that this focus neglects a critical role of international trade: creating tension between states that sell similar goods to the global market. We consider this role explicitly and operationalize its effects empirically. Using commodity-level trade data from 1962 to 2000, we show that countries that produce and sell similar goods are generally more likely to fight, even after we take into account their bilateral trade ties and institutional membership in the global economic system. Our findings are robust to numerous alternative specifications and suggest a strong relationship between economic competition in the global market and military conflict between states.